The privatization of education as a project: private sector and High School in Mato Grosso (Olhar de Professor, 2024)
The objective of this article is to understand ways of inserting the private sector in public high school in the state of Mato Grosso, based on the adoption of the Structured Education System. The context of the 1990s is presented as encouraging partnerships with the private sector, given the supposed efficiency of its management. The purchase of handout material, by the public sector, is linked to the discourse of superiority in the method of private schools, disregarding the specificities of public administration. It was possible to identify, with the bibliographic and documentary survey, in the Mato Grosso proposal, the material apostilled in the dynamics of the 10-year EducationAction Plan, which aims to place the network among the five best evaluated public networks in the country by 2032, combined with the Connected Schools Platform and the Plurall digital platform, which contains the version digital of the materials, with complementary activities. The privatization of education is considered a long-term project, that has been coming to fruition.
Keywords: Privatization of education; Structured Education Systemem; High School